Realizing Gender Equality in Basic Education in Indonesia: An Analysis of Challenges, Policies, and Responsive Practices - Maulana, Faris; Aristamia Sukma Ayuningtyas; Sayidah Nabilah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study comprehensively analyzes the implementation of gender equality in Indonesian basic education. Its objectives are to identify challenges, review relevant government policies, explore implemented best practices, and measure their impact on student character development and sustainable development achievements. The research method employs a qualitative approach, based on a comprehensive analysis of academic literature, research reports, and relevant government policy documents. Findings indicate that despite strong legal frameworks guaranteeing gender equality, implementation in basic education faces crucial challenges. These include gender bias in curriculum and teaching materials, discrimination in educational access exacerbated by economic and cultural factors, the pervasive influence of patriarchal culture, and a lack of teacher understanding regarding gender bias. However, programs like Gender-Responsive Schools (SRG) and non-formal education institutions (PKBM) demonstrate promising practices in addressing these challenges. The positive impacts observed include changes in student mindset and behavior (increased empathy and respect), enhanced female participation and confidence, and significant contributions to achieving the Sustainable Development Goals (SDGs). In conclusion, while challenges persist, planned and collaborative interventions among government, schools, teachers, and parents are crucial for realizing fair and inclusive education for all children.